Visiting a "frail elderly": A review on model of care and treatment strategies - Tarun Rao; Vishakha Jain; A P Jain (Wolters Kluwer Medknow Publications, 2016)
Frail elderly are those who have less than normal physiological reserve which predisposes them to more severe adverse outcomes following a stressor compared to normal. As the number of elderly is increasing worldwide, there is increase in the problem of frailty. Frailty is a dynamic state in the sense that if interventions are directed to correct the state of frailty, then an elderly starts to shift toward normal side and if not then deteriorated even more. When it comes to managing a frail elderly, then the place of care can be patientfs home as well as health care facility. Comprehensive geriatric assessment and program for all.-inclusive care for the elderly are the concepts that advocate multidisciplinary approach for the management of frail elderly. There is increasing evidence in favor of the management of these patients at their home and delaying the transfer to health care facility till these patients cannot be managed at home. Apart from the specific treatment of the acute illness and the underlying chronic illness, there are other interventions cum life style modification which can help in improving a frail state. These includes increasing content of whey protein, essential amino acids in the diet, combination of resistance and endurance exercises, Vitamin D supplementation, and pharmacotherapy such as testosterone, ghrelin, and growth hormone.